Design for remanufacturing in China: A case study of electrical and electronic equipment - Gillian D. Hatcher; Winifred L. Ijomah; James F. C. Windmill (Journal of Remanufacturing, 2013)
As global demand for consumer goods continues to rise, the problem of waste electrical and electronic equipment (or e-waste) increases. E-waste is of particular concern to the world's governments and environmentalists alike, not just because of the sheer quantity that is being produced annually, but also because e-waste often contains both hazardous materials and scarce or valuable materials. Much research is now focused upon how this waste can be treated safely, economically, and in an environmentally sound manner. This paper presents the findings from a literature review and case study research conducted as a small part of the Globally Recoverable and Eco-friendly E-equipment Network with Distributed Information Service Management (GREENet) project. The GREENet project aims to share knowledge and expertise in e-waste treatment across Europe (in this case, the UK) and China. The focus of this particular study was upon 'design for remanufacture' and e-waste in China: as a remanufacturing industry begins to emerge, are Chinese original equipment manufacturers (OEMs) prepared to design more remanufacturable products and could electrical and electronic products become a part of this industry? Findings presented in this paper suggest that design for remanufacture could become more relevant to Chinese OEMs in the near future, as environmental legislation becomes increasingly stringent and a government remanufacturing pilot scheme expands. However, findings from case studies of Chinese e-waste recyclers would suggest that electrical and electronic products are not presently highly suited to the remanufacturing process.
Keywords: 650; E-waste; design for remanufacture; recycling; China; Elektronikschrott; Betriebliche Kreislaufwirtschaft; Produkt-Recycling; Produktgestaltung; China